On the Development of a Vibration Energy Harvesting Mechanism and the Influence of the Number of Wire Turns - Wiwiek Hendrowati; Bambang Daryanto W Daryanto W; I Nyoman Sutantra (IPTEK The Journal for Technology and Science, 2010)
This article deals with a research activity to design and to build a vibration energy harvesting (VEH) mechanism based on an electromagnetic method, where the energy source is from translational-harmonic vibration. In the developed VEH mechanism, a magnetic mass moves linearly back and forth within an electrical coil made from conductive-wire windings. In accordance to oscillating mass motion of a particular amplitude and frequency, the voltage which can be harvested is then measured and analyzed. The choice of an electromagnetic method stemmed from the availability of materials to construct the VEH mechanism. In the VEH mechanism, a mass size, a wire diameter and material, a coil length, and a vibration amplitude and frequency were considered constant, while the number of wire turns was varied. The constructed VEH was tested for 1,000, 1,500, 2,000, 2,500, and 3,000wire turns. The voltage density being harvested was recorded as 0.2820, 0.3715, 0.5695, 0.7343 and 0.9300 volt/cm3, respectively.